Prognostic Significance of “In hospital Arrythmias” in Acute Myocardial Infarction - Verma, Y; Singh, CM; Gupta, R; Sharma, VK; Singh, G; Shrivastava, RK; Meena, RS; Himthani, Naresh (Nepalese Heart Journal, 2004)
Arrythmias after Acute myocardial infarction (AMI) have a prognostic value, in addition to the morbidity it involves. To evaluate the significance of arrythmias 50 patients of AMI (37-Male, 13-Female) in the age group of 35-72 years were studies, Out of these 50 cases, 48% (n=24) had anterior wall myocardial infarction, 30% (n-15) had inferior wall myocardial infarction, 22% (n=11) had interior+Right Ventricular wall myocardial infarction. Thrombolysis was done in 56% (n=28) patients fulfilling inclusion criteria. Left ventricular ejection fraction (LVEF) of less than 50% was present in 24% (n=12) patients. 50% patients (n=25) experienced “In hospital arrythmias” and 28% (n=7) patients had cardiac events in 6 months follow up. In the group without “In hospital arrythmias" 60% (n-15) developed follow up events. Out of 12 patients with LVEF of less than 50% (n=12), 8 patients (66%) developed “In Hospital arrythmias” and 10 patients (83%) developed subsequent morbid cardiac events.